Seropositivity to Midichloria mitochondrii (order Rickettsiales) as a marker to determine the exposure of humans to tick bite. (19th May 2019) - Serra, Valentina; Krey, Viktoria; Daschkin, Christina; Cafiso, Alessandra; Sassera, Davide; Maxeiner, Horst-Günter; Modeo, Letizia; Nicolaus, Carsten; Bandi, Claudio; Bazzocchi, Chiara
ABSTRACT: Ixodes ricinus is the most common tick species parasitizing humans in Europe, and the main vector of Borrelia burgdorferi sensu lato, the causative agent of Lyme disease in the continent. This tick species also harbors the endosymbiont Midichloria mitochondrii, and there is strong evidence that this bacterium is inoculated into the vertebrate host during the blood meal. A high proportion of tick bites remains unnoticed due to rarity of immediate symptoms, implying the risk of occult tick-borne infections in turn a potential risk factor for the onset of chronic-degenerative diseases. Since suitable tools to determine the previous exposure to I. ricinus bites are needed, this work investigated whether seropositivity toward a protein of M. mitochondrii (rFliD) could represent a marker for diagnosis of I. ricinus bite. We screened 274 sera collected from patients from several European countries, at different risk of tick bite, using an ELISA protocol. Our results show a clear trend indicating that positivity to rFliD is higher where the tick bite can be regarded as certain/almost certain, and lower where there is an uncertainty on the bite, with the highest positivity in Lyme patients (47.30%) and the lowest (2.00%) in negative controls. According to the obtained results, M. mitochondrii can be regarded as a useful source of antigens, with the potential to be used to assess the exposure to ticks harboring this bacterium. In prospect, additional antigens from M. mitochondrii and tick salivary glands should be investigated and incorporated in a multi-antigen test for tick bite diagnosis.